Strategic Digital Communicative Design for Emerging Fashion Brands - Ressa Uli Patrissia; Nadia Adiva Putri Pertiwi (UPT Publikasi Ilmiah UNISBA, 2026)
Hayara.id is a premium hijab brand targeting digitally native Muslim women in Indonesia, whose website experienced a significant decline in user sessions and engagement. This study investigates how theory-driven website interventions can enhance digital brand recognition by integrating behavioral, algorithmic, emotional, and symbolic communication strategies. The research pursues two objectives: (1) to develop a communication-based website branding framework and (2) to evaluate the impact of a strategic website redesign on brand awareness and user engagement. To achieve these objectives, the study introduces the Digital Resonance Branding Model (DRBM), synthesizing the AISAS model, Algorithmic Identity Theory, Communicative Figurations, and Emotional Branding. A three-month intervention comprised SEO-oriented information architecture restructuring, UX/UI optimization aligned with AISAS stages, emotional storytelling through blog and visual content, and symbolic brand identity refinement. Using a practice-based research approach, findings were triangulated across Google Analytics, Hostinger Builder metrics, and stakeholder interviews. Post-intervention results show a 206% increase in sessions, a 74% rise in unique visitors, a 48% reduction in bounce rate, and a 1266% increase in checkout clicks. These findings indicate that digital brand awareness is shaped by recursive behavioral, algorithmic, and symbolic interactions rather than visibility alone. DRBM offers a replicable framework for emerging fashion brands seeking emotionally resonant, identity-driven web experiences.